1975
DOI: 10.1002/1097-0142(197502)35:2<464::aid-cncr2820350225>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary polyamine levels in human cancer

Abstract: Polyamine levels (putrescine, spermidine, spermine) were determined in 24‐hour urine samples by a high voltage electrophoresis technique. Normal values were established in 42 normal volunteers. Thirty‐eight of 56 patients with metastatic cancer had two or more levels elevated. Approximately two‐thirds of patients with metastatic adenocarcinoma. metastatic squamous cell cancer or metastatic disease to the liver, lungs, or bones had elevated levels. All 6 patients with localized malignant tumors had elevated uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Increased urinary and serum polyamine levels occur in association with a wide variety of malignancies, including carcinomas of the gastrointestinal tract, ovary, breast, and prostate, sarcomas, lymphomas, and leukaemias (Russel et al, 1971;Denton et al, 1973;Fair, 1975;Lipton et al, 1975;Marton et aI., 1973). Most of the subjects, however, had advanced disease.…”
Section: Biochemical Monitoring Of Cancer 295mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased urinary and serum polyamine levels occur in association with a wide variety of malignancies, including carcinomas of the gastrointestinal tract, ovary, breast, and prostate, sarcomas, lymphomas, and leukaemias (Russel et al, 1971;Denton et al, 1973;Fair, 1975;Lipton et al, 1975;Marton et aI., 1973). Most of the subjects, however, had advanced disease.…”
Section: Biochemical Monitoring Of Cancer 295mentioning
confidence: 99%
“…However, inflammatory and regenerative conditions can also lead to increased levels thereby vitiating any useful role (Lipton et al, 1975). Nonetheless, they may be of some value to monitor the efficacy of surgical and chemotherapeutic regimes (Russel et al, 1971;Denton et al, 1973), but further detailed clinicopathological studies with improved methods (Marton et al, 1973) are needed before their place in cancer monitoring can be truly assessed.…”
Section: Biochemical Monitoring Of Cancer 295mentioning
confidence: 99%
“…Since Russell (1971) first reported that cancer patients excreted an increased amount of polyamines in their urine, a number of papers have been published on raised polyamine levels in urine (Dreyfuss et al, 1975;Lipton et al, 1975;Waalkes et al, 1975) and plasma or serum (Nishioka & Romsdahl, 1974;Russell & Russell, 1975;Nishioka & Romsdahl, 1977;Nishioka et al, 1977;Chaisiri et al, 1979) of cancer patients. At present, however, the clinical application of polyamine determinations as a diagnostic tool for cancer detection has been limited by the low sensitivity and lack of specificity of polyamine detection in urine or plasma.…”
mentioning
confidence: 99%
“…A B S T R A C T The serum and urine polyamines putrescine, spermidine, and spermine were measured in 112 normal subjects from 0 to 70 yr of age, and in three groups of short children from 7 to 20 yr: 21 growth hormone (GH) deficient patients, 20 normal variant short stature children, and 9 girls with 45, X Turner's syndrome. Urine polyamines were expressed as micromoles per gram of creatinine or per kilogram body weight, and serum polyamines were expressed as nanomoles per milliliter.…”
mentioning
confidence: 99%